THE EFFECT OF VITAMIN D IN KIDNEY FUNCTION AND THYROID GLAND - & Hilal, Al-Sa’ady (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to determine the role of vitamin D on renal function and thyroid gland. Eighty blood samples were collected (20 patients and 20 healthy) of different sex with different ages (28-88) years from Baghdad’s hospitals to study the renal function, as well as samples from (20 patients and 20 healthy) of different sex with various ages (12-62) years were collected to study the thyroid gland function. The blood samples of kidney were tested for urea, creatinine and vitamin D, whereas other samples tested for Thyroid stimulating hormone (TSH), Thyroxine (T4), and Tri-iodothyronine (T3), and vitamin D. The results were shown that 70.4% from renal patients have vitamin D deficiency, whereas 29.6% of a healthy individual also suffering from vitamin D difficult. Furthermore, the relative risk (RR) was 9.15 of cohort renal patient. On the other hand, there were weak correlation between gender and age with vitamin D level. Also, the results reveal that 84.6 % of patient with thyroid were suffering from vitamin D deficient and 15.4 % of healthy individual also suffering from vitamin D deficient, therefor the relative risk (RR) was 2.54 of cohort thyroid patient. And there were no significant relationship between gender, age with vitamin D level in patient with thyroid.